Effects of Structural Adjustment Programs in the Mining Industry on Women in Zambia - Barankariza, Irene (Université d'Ottawa / University of Ottawa, 2016)
Notwithstanding the many claims about the advantages of extracting minerals and about the level of demand for these commodities, the existing literature has shown that Zambian mines rarely benefit their host communities. This study details the challenges and opportunities perceived by women who work and live in the Kalulushi and Kitwe mining communities of Zambia. Drawing on contemporary Marxist feminist theory and on transnational feminist theory, a qualitative research design was applied whereby in-depth interviews were conducted with 18 women from the Kalulushi and Kitwe mine communities with the goal of assessing the challenges and opportunities perceived by these women, whether as formal or informal mine workers, or as homemakers. The findings show that, while some of the interviewed women have been negatively affected by Structural Adjustment Programs, others state that they have not been impacted at all. As such, this study points towards areas for future research.